The Implementation Of T-Ex Approach On The Short Story Teaching In Efl Class - Maru, M G (Universitas Negeri Manado, 2019)
This research aims at applying the jeremiad approach in literary class particularly using short story for the purpose of finding a proper teaching design or model for character education. It is further hoped to obtain a teaching model on the text-based learning for the purpose of improving the quality of teaching of English as Foreign language (EFL) and the shaping of students’ character. These purposes will be gained through qualitative inquiry which is marked by the involvement of students as the respondents and the researchers in its implementation. The students will be considered as the objects of this study. Those students involves in British and American Prose class in English Education Department, Universitas Negeri Manado. They will be taught using the Jeremiad Approach and later will be observed as well as interview. The data of the research are mostly taken from the result of interview and observation. The interview is done with the questions of how the shaping of their character as short story is used by combining it with the jeremiad approach. The observation is carried out through students’ intellectual diary which is written in every meeting. The data are analyzed and coded in the way of Grounded Theory. The findings show the implementation of the T-Ex approach had provided students the opportunities to involve in active sharing and discussion within which they observed, questioned, tried, associated, comprehended, analyzed, created, presented, implemented, respected, experienced, and accepted as well as evaluated. In addition, the use of the students’ intellectual diaries, a kind of daily note, contributed not only to monitor the advantage of the approach to the class but also alternatively to assess authentically students’ absorption as well as competency outputs.Keywords: T-Ex Approach, Shortstory, EFL Class, Character Education